FRAMEWORK FOR OPTIMIZING ORGANIZATIONAL DATA MANAGEMENT VIA WEB-BASED SYSTEMS AND RELATIONAL DATABASES: EMPIRICAL INSIGHTS FROM SMES AND PUBLIC LIBRARIES - awalliyah, siti_; Furqan Ramadhan, Rizal; Rusmanysah, Iyus; Lisnawati, Tuti (Buana Informatika, 2025)
This research aims to design and evaluate an information system or technology-based application specifically developed to enhance efficiency and accuracy in data management. In today’s rapidly evolving digital landscape, organizations face increasing demands for reliable, high-performance systems capable of managing complex datasets with precision and speed. To meet these demands, this study focuses on the creation of a robust system that not only fulfills functional requirements but also ensures optimal performance, user-friendliness, and scalability for potential integration into various operational environments. The system was developed through a structured and systematic methodological approach, encompassing key stages in the software development lifecycle. These stages included comprehensive requirement analysis, conceptualization and design of the system architecture, implementation of modular components, and rigorous testing of both functionality and overall system performance. Each phase was carried out iteratively to ensure alignment with end-user expectations and to identify and mitigate potential issues early in the development cycle. This phased methodology contributed significantly to minimizing errors during deployment and ensured that the final product met all specified performance benchmarks. The data used in this study were collected through simulations and real-world usage scenarios to ensure high validity and reliability in practical implementation contexts. Simulated data allowed for.